A cartography of al-Andalus' landscape: Mapping settlements of Muslim agricultural colonization in Europe applying GIS techniques. (July 2022) - Quesada-García, Santiago
Abstract: This paper analyses the landscape defined by rural settlements, with Hispanic Muslim remnants built in a rammed-earth technique in a valley located in the south-eastern Iberian Peninsula. The aim of this work is to describe the different anthropic points of this particular medieval landscape to contextualize them in the historical literature and then to expose, alongside the methodological innovations applied, the main behavioural patterns found in the implantation of these establishments in order to categorize and classify them. This challenge involves using procedures that enable a macrospatial reading of the territory and measurement of the influence of landscape variables. In order to achieve this goal, an original and interdisciplinary method has been designed combining archaeological, historical, and architectural techniques alongside a multicriteria analysis developed in the geographic information systems setting. The findings provide significant knowledge about the ways in which the al-Andalus' territory was populated, how the system of rural nodes worked, and the relationships between establishments and agricultural colonization, shedding new light on the complex palimpsest of landscape. A video component is available to introduce this landscape, which you can access by clicking on the image below (video 1). Highlights: A new territorial characterization of rural settlements in al-Andalus. Revealing new sources of information to study the landscape of the Middle Ages. An innovative methodology for assessing and comparing the features of the territory. Extracting quantifiable geomorphological data from rural heritage landscapes. An essential cartography to understand the agricultural colonization in al-Andalus.